Pengaruh Financial Distress, Ukuran Perusahaan, Reputasi KAP, Opini Audit Sebelumnya Pada Opini Audit Going Concern - Napitupulu, Hanna Ewita; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p13, 2022)
The auditor's responsibility in identifying the ability to maintain his client's business in the long term is an issue that is rarely revealed because fraudulent practices are still being found in the field. The purpose of this research is to empirically prove the effect of financial distress, company size, KAP reputation, previous audit opinion on “going concern” audit opinion. The research was conducted on property & real estate companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The research sample amounted to 46 samples of companies using purposive sampling method. The data analysis technique used is logistic regression analysis. The results showed that financial distress did not have a positive effect on the “going concern” audit opinion, company size and reputation of the public accounting firm (KAP) had a negative effect on the “going concern” audit opinion. While the previous audit opinion has a positive effect on the "going concern" audit opinion. Keywords: Going Concern; Financial Distress; Size; KAP Reputation; Previous Audit Opinions.